(untitled) (Asian Journal of Plant Biology, 2023)
Bambara groundnut is cultivated by low-income earning farmers at the subsistence level without knowledge of genetic diversity on major morphological and yield traits. This study aimed to assess morphological variations and crop performance among commonly cultivated Bambara groundnut landraces. The five most commonly cultivated Bambara groundnut landraces were collected from farmers and were planted randomly in a complete block design (RCBD) with three replications in the Botanical Garden of Gombe State University. The results of the analysis of variance from this study revealed significant variation among some of the traits. The results on germination percentage showed that the landraces germinated between seven to ten (7-10) days after planting with 73% and 100% as the lowest and highest mean percentages. The highest mean number of leaves observed was in Stripped Black 122 whereas the lowest mean was 52. The highest mean observed at ten weeks after planting was 31.20 and the lowest mean was 23.00 in stripped brown and stripped black landraces. The highest mean plant canopy spread observed was 70cm in the white landrace, whereas the lowest mean plant canopy observed was 35cm in the black landrace. The highest mean biomass fresh weight observed was 214.95 among the white landrace while the lowest mean observed was 80.30 among the red landrace. A similar trend was recorded on biomass dry weight where the white landrace recorded 101.23 while the red landrace recorded the lowest mean biomass dry weight at 30.62 these traits have highlighted the significance chosen various parameters in selection for breeding and improvement of Bambara groundnut.